Periodic colour-centre structure formed under filamentation of mid-IR femtosecond laser radiation in a LiF crystal. (April 2016) - Kuznetsov, A.V.; Kompanets, V.O.; Dormidonov, A.E.; Chekalin, S.V.; Shlenov, S.A.; Kandidov, V.P.
Abstract: A colour-centre structure formed in a LiF crystal under filamentation of a femtosecond mid-IR laser pulse with a power slightly exceeding the critical power for self-focusing has been experimentally and theoretically investigated. Strictly periodic oscillations have been detected for the first time for the density of the colour centres induced in an isotropic LiF crystal under filamentation of a laser beam with a wavelength tuned in the range from 2600 to . The structure period is found to be about . With an increase in the laser radiation wavelength, the period of the oscillations decreases and their amplitude increases. The maximum colour centre density, observed under filamentation of a beam, is related to the increased contribution of the direct generation of colour centres as a result of the absorption of an integer number of photons by the exciton band. It is numerically shown that the formation of a periodic colour-centre structure in LiF is due to the periodic change in the light field amplitude in the light bullet (1.5 optical periods long) formed under filamentation.